KLASIFIKASI VEGETASI GUNUNG ENDUT, TAMAN NASIONAL GUNUNG HALIMUN-SALAK, BANTEN - Sambas, EN; Kusmana, C; Prasetyo, LB; Partomihardjo, T (BERITA BIOLOGI, 2011)
The research objective is to classify the variety of vegetation types at Mount Endut, Gunung Halimun-Salak National Park. Vegetation sampling was carried out with systematic sampling with random start. Vegetation type at alliance level was determined with vegetation ordination using factor analysis. Four vegetation alliances can be extracted from the ordination. These alliances are Castanopsis acuminatissima-Schima wallichii/Freycinetia javanica (alliance 1); Castanopsis argentea-Dendrocnide stimulans/Schismatoglottis calyptrata (alliance 2); Coffea canephora var. robusta-Quercus lineata/F. javanica( alliance 3) and Paraserianthes falcataria-Coffea canephora var. robusta/Oplismenus compositus (alliance 4). Vegetation alliances form due to their similarity in structure, composition, and physiognomy of vegetation. There are four vegetation associations at alliance 1, i.e. Castanopsis acuminatissima vegetation association, Schima wallichii vegetation association, Garcinia rostrata vegetation association, and Quercus lineata- Eurya acuminata /Freycinetia javanica vegetation association. Alliance 2 has four vegetation associations i.e.Dendrocnide stimulans vegetation association, Coffea canephora var. robusta vegetation association, Castanopsis argentea -Castanopsis acuminatissima vegetation association, and Schismatoglottis calyptrata-Etlingera coccinea vegetation association.There are seven vegetation associations belonging to alliance 3 i.e. Castanopsis acuminatissima vegetation association, Coffea canephora var. robusta vegetation association, Quercus lineata vegetation association, Garcinia rostrata-Schima wallichii vegetation association, Euodia latifolia - Pternandra azurea/Schismatoglottis calyptrata vegetation association, Raphidophora foraminifera vegetation association, and Freycinetia javanica vegetation association. Alliance 4 has five vegetation associations i.e Paraserianthes falcataria vegetation association, Coffea canephora var. robusta vegetation association, Maesopsis eminii/ Erechtites valerianifolia - Clidemia hirta vegetation association, Oplismenus compositus vegetation association, and Clibadium surinamense vegetation association.